Destination personality and destination image. (September 2017) - Souiden, Nizar; Ladhari, Riadh; Chiadmi, Nour Eddine
Abstract: This study examines the impacts of destination personality and image on individuals' attitudes and visiting intentions. Based on a sample of 173 Canadians, the study investigates the impact of the perceived personality and image of the city of Dubai on respondents' attitudes and visiting intentions. The results show that destination image is an antecedent to destination personality, which in turn has a direct impact on attitude toward a destination and an indirect effect on behavioural intentions. The results have important theoretical implications for academics and offer intriguing managerial suggestions for destination marketers and public policy-makers.